Design and Test Wireless Pedicle Probe for Spine - Zina Ali Abed, Ziad Tarik Ai-Dhhan (Pakistan Journal of Medical & Health Sciences, 2022)
pedicle screw placement in spinal fixation surgery is a very challenging technique especially for those patients with scoliosis and degenerative diseases, due to variation in the vertebral structure between different levels of the spine and between humans, Also due to the site of placing the screw in the pedicle, it’s near the nerve roots of the spine, But recently there was excessive effort to reduce the risk of this surgery by inventing new methods to override these risks, Wireless probe was created in this test by using ESP32 Wifi and Bluetooth development board as a processer, And Raspberry Pi3 Model B+ to display the result, By using Force sensor (FSR 400) and Hall effect sensor (AH49E) to detect bone density variation of the vertebral body and distinguish between cortical and cancellous bone, The test was performed on a three years old calf vertebra from the thoracic region and the result has been taken in a different situation to prove that the probe is working.